Iodine deficiency among pregnant women living in Northern Ireland. (12th August 2019) - McMullan, Paul; Hamill, Lesley; Doolan, Katy; Hunter, Alyson; McCance, David; Patterson, Chris; Smyth, Peter; Woodside, Jayne V.; Mullan, Karen
Abstract: Objective: Mild iodine deficiency has re‐emerged among school girls in the UK. We wished to study a contemporaneous pregnant population because a relationship between maternal iodine deficiency and offspring cognitive scores has recently been reported. The WHO has set a median population urinary iodine concentration (UIC) of ≥100 and ≥150 µg/L to define adequacy outside of and during pregnancy, respectively. Iodine creatinine ratio (ICR) is also used to correct for dilution effects (sufficiency ≥150 µg/g creatinine in pregnancy). Design and methods: A total of 241 women were followed across trimesters (T) into the postpartum period (PPP) along with 80 offspring with spot urine sampling and food frequency questionnaires. Results: Median UIC was 73 µg/L in the 1st T (ICR 102 µg/g creatinine) despite 55% taking iodine‐containing supplements. Median UICs were 94, 117 and 90 µg/L in the 2nd T, 3rd T and PPP, respectively. Corresponding ICRs were 120, 126 and 60 µg/g creatinine. ICR was associated with volume of milk consumed throughout pregnancy. Median UIC among the offspring was 148 µg/L, with no difference between the breast‐ and formula‐fed babies. Conclusions: Pregnant women living in Northern Ireland may be at risk of iodine deficiency across pregnancy and into the PPP while the offspring are iodine sufficient. This is the first study of its kind in the UK with data for pregnant women and their offspring. The UK does not provide an iodine fortification programme nor offer routine iodine dietary advice in pregnancy and this requires consideration by public health agencies.